TRANSFORMASI STRATEGIS ASURANSI SYARIAH DALAM MENINGKATKAN KONTRIBUSI TERHADAP EKONOMI SYARIAH NASIONAL - Reza Ronaldo; Yul Maulini (Juremi: Jurnal Riset Ekonomi, 2025)
Strengthening the Islamic insurance (takaful) sector in Indonesia plays a strategic role in accelerating the growth of the national sharia economy. Despite being home to the largest Muslim population in the world, the contribution of Islamic insurance to the total national insurance premium remains relatively low, only around 7.8% or approximately IDR 16 trillion, significantly lagging behind conventional insurance premiums, which reached IDR 204.2 trillion. This study aims to examine and formulate effective strategies to enhance market penetration and the contribution of Islamic insurance to the national economy. Employing a descriptive qualitative approach, data were collected through in-depth interviews, document analysis, and focus group discussions (FGDs) involving key stakeholders. The findings indicate that the acceleration of the Islamic insurance industry is strongly influenced by three critical factors: product innovation, improvement of Islamic financial literacy, and cross-sector collaboration among the government, industry players, and educational institutions. Regulatory constraints and limited public trust must be addressed through proactive policies and sustained educational campaigns. This study recommends the pentahelix model as an integrated strategic framework to reinforce the role of Islamic insurance in supporting the development of Indonesia’s sharia-based economy.